Pharmacogenetic characterization of naturally occurring germline NT5C1A variants to chemotherapeutic nucleoside analogs. Issue 6 (June 2016) - Saliba, Jason; Zabriskie, Ryan; Ghosh, Rajarshi; Powell, Bradford C.; Hicks, Stephanie; Kimmel, Marek; Meng, Qingchang; Ritter, Deborah I.; Wheeler, David A.; Gibbs, Richard A.; Tsai, Francis T.F.; Plon, Sharon E.
Abstract : Background: Mutations or alterations in expression of the 5′ nucleotidase gene family can lead to altered responses to treatment with nucleoside analogs. While investigating leukemia susceptibility genes, we discovered a very rare p.L254P NT5C1A missense variant in the substrate recognition motif. Given the paucity of cellular drug response data from the NT5C1A germline variation, we characterized p.L254P and eight rare variants of NT5C1A from genomic databases. Materials and methods: Through lentiviral infection, we created HEK293 cell lines that stably overexpress wild-type NT5C1A, p.L254P, or eight NT5C1A variants reported in the National Heart Lung and Blood Institute Exome Variant Server (one truncating and seven missense). IC50 values were determined by cytotoxicity assays after exposure to chemotherapeutic nucleoside analogs (cladribine, gemcitabine, 5-fluorouracil). In addition, we used structure-based homology modeling to generate a three-dimensional model for the C-terminal region of NT5C1A. Results: The p.R180X (truncating), p.A214T, and p.L254P missense changes were the only variants that significantly impaired protein function across all nucleotide analogs tested (>5-fold difference vs. wild-type; P <0.05). Several of the remaining variants individually showed differential effects (both more and less resistant) across the analogs tested. The homology model provided a structural framework to understand the impact of NT5C1A mutants on catalysis and drug processing. The model predicted active site residues within NT5C1A motif III and we experimentally confirmed that p.K314 (not p.K320) is required for NT5C1A activity. Conclusion: We characterized germline variation and predicted protein structures of NT5C1A. Individual missense changes showed considerable variation in response to the different nucleoside analogs tested, which may impact patients' responses to treatment. Abstract : Supplemental Digital Content is available in the text.